2019
DOI: 10.1016/j.gaceta.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Consecuencias del dolor crónico en la infancia y la adolescencia

Abstract: This Scoping Review shows that functional capacity, sleep, personal development, peer support and family functioning are interesting lines in published works. However, gaps in knowledge are detected in areas such as risk behaviours, the consequences that pain can cause in adulthood and gender inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
1
1
1
Order By: Relevance
“…Youssef et al [ 34 ] stated that, although children with chronic pain showed a higher number of school absences, there was no associated comorbidity. This statement contrasts with data obtained in other recent investigations, where school absenteeism was shown to interfere with school functioning, lack of meeting with friends, inability to play sports, bullying, and harassment as well as teachers and peers’ mistreatment [ 55 , 56 , 57 ]. Therefore, pain seems to generate school absenteeism inducing a negative effect on the students’ participation in school activities.…”
Section: Discussioncontrasting
confidence: 97%
“…Youssef et al [ 34 ] stated that, although children with chronic pain showed a higher number of school absences, there was no associated comorbidity. This statement contrasts with data obtained in other recent investigations, where school absenteeism was shown to interfere with school functioning, lack of meeting with friends, inability to play sports, bullying, and harassment as well as teachers and peers’ mistreatment [ 55 , 56 , 57 ]. Therefore, pain seems to generate school absenteeism inducing a negative effect on the students’ participation in school activities.…”
Section: Discussioncontrasting
confidence: 97%
“…Research on chronic pediatric pain abounds in the evaluation of etiology, pathophysiological factors, diagnostic processes, pharmacological, and physical treatments (Blackman, Svensson, & Marchand, 2018; Gmuca et al, 2018; Orava, Provvidenza, Townley, & Kingsnorth, 2018; Pas et al, 2018; Riquelme, do Rosário, Vehmaskoski, Natunen, & Montoya, 2018; Sheehy et al, 2015); on the contrary, although some lines of research exist (Cáceres-Matos, Gil-García, Barrientos-Trigo, Molina, & Porcel-Gálvez, 2019; Vega et al, 2018; Yetwin, Mahrer, John, & Gold, 2018), current data are more lacking in the evaluation of non-physical variables associated with chronic pediatric pain and related potentially complementary interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Überdies sind Analgetika zumeist wirkungslos [9]. All dies führt bei den Betroffenen häufig zu einem Gefühl der Hilflosigkeit, zu Alltagseinschränkungen, sozialem Rückzug und erheblichen Folgekosten [10,11]. Chronische Schmerzen bei Kindern und Jugendlichen verstärken v. a. aber die psychische Belastung, da sich reduzierter Schulbesuch, verminderte Frei-zeitaktivitäten, Schlafprobleme und eingeschränkte Unternehmungen mit Freund*innen und Familie zunehmend auf das emotionale Wohlbefinden auswirken.…”
unclassified